One-pot Synthesis and the Biological Activities of 4-Methylpyrano[3,2-C]-quinolin-2,5-[6H]-diones - Venkatesh Kumar, N.; Rajendran, S.P. (Asian Journal of Chemistry, 2016)
One step synthesis, starting from 4-hydroxy-2-quinolone with ethyl acetoacetate and pyridine proceeded through the Michael addition, gave an angular isomer 4-methylpyrano[3,2-c]quinolin-2,5[6H]-dione. The reaction sequence was then extended to synthesize further derivatives of angular pyrano quinolones. Structures of all the products have been established by spectral and elemental analysis data. The antibacterial activity against various bacterial strains like Escherichia coli, Bacillus subtilis, Aeromonas hydrophilla, Staphyloccocus aureus and Klebsiella pneumoniae have also been investigated.